War on the edge of Europe: The Chechen conflict in a new light? - Uwe Halbach (Stiftung Wissenschaft und Politik (SWP), 2002)
The Moscow hostage drama has brought the war in Chechnya back into public discussion. Spectacular kidnappings with large numbers of casualties were a feature of the escalation of violence in the North Caucasus in the past. But never did the outpouring of violence from the war in Chechnya strike Russia and the rest of the world as directly as it did this time. The Russian Government's official position on the act of terrorism in Moscow, and its alleged link with international terrorism, is an occasion to re-examine some aspects of the long war in the North Caucasus region. (SWP Comments / SWP)
Keywords: 320